Writing for public relations and strategic communication - Thompson, William, 1955-; Browning, Nicholas (San Diego : Cognella, 2022)
Writing for Public Relations and Strategic Communication equips students with the knowledge, skills, and tools they need to write persuasively. The book underscores the importance of strategic analysis at the beginning of the writing process. Utilizing an audience-centered perspective, it shows how persuasive writing emerges organically after critically assessing the goals of an organization's message in light of its intended audience. Students learn essential strategic thinking and planning skills to create effective and intentional writing. The book presents the theoretical underpinnings of behavior, which students can then employ to generate prose that prioritizes the audience's reasons for attending to the message. The book is unique in presenting a primer on communication, persuasion, and moral theories that provides students a roadmap for constructing effective, ethical arguments. Throughout, anecdotes, examples, quizzes, and assignments help connect theory to practical, real-world applications. Writing for Public Relations and Strategic Communication helps readers build their persuasive writing skills for professional and effective public relations, employing unique strategies and tactics, such as: - A generative writing system that helps students identify and organize important information to produce quality prose, then adapt it to various media, on deadline - Interactive walkthroughs of writing examples that deconstruct prose, offering students insights not just into what to write, but how and why practitioners make strategic choices-down to the word level - Long-form scenario prompts that allow students to hone their persuasive writing, editing, and communication management skills across an array of platforms - Three two-chapter modules where the first chapter demonstrates how to write effective prose for a particular channel and the second offers practical help in delivering those products through message-delivery channels - Detailed case studies demonstrating how to translate research and planning into storytelling that addresses organizational problems - Unique chapters building important analytical literacies, such as search engine optimization tactics, marketing statistics analysis and data-driven audience targeting methods.
PART I. Think First, Write Second. -- 1. Communication Theory in Real Life -- 2. Transforming Communication Theory Into Working Models of Persuasion -- 3. Creative Communication Planning -- 4. Market Research and Targeting -- 5. Ethical Issues for Persuasive Writers -- PART II. How to Write Strategically. 6. Reaching the Right Audience Right Now -- 7. Building a Persuasive Case -- 8. Adding Sensory Channels -- 9. Fostering Interactivity -- PART III. Executing Tactics to Serve a Goal. 10. The Audience to Reach an Audience -- 11. Delivering Uncontrolled Messages -- 12. When the Organization Controls the Message -- 13. Delivering and Evaluating Controlled Messages -- 14. New Media, Old Tricks -- 15. Say Something,Then Be Ready for Anything.
Includes bibliographical references (pages 397-409)and index.
Keywords: Public relations; Public relations -- Authorship; Communication in marketing; Public Relations; Relations publiques; Communication en marketing; public relations; Communication in marketing; Public relations; Public relations -- Authorship